Expression profiles of Wnt genes during neural differentiation of mouse embryonic stem (ES) cells - Nordin, Norshariza; Meng, Li; Mason, John O. (2009)
One important use of embryonic stem (ES) cells is to provide an ideal system in which to study genetic mechanisms that regulate differentiation along specific lineages. Once such differentiation can be precisely controlled in vitro, ES cells would be useful for a variety of therapeutic applications including a potential source of transplantable neurons in treating neurodegenerative diseases. Improved understanding of the mechanisms that drive neural differentiation of ES cells is hoped to enhance the prospects for generating pure populations of defined neuronal subtypes. Increasing evident clearly shows the involvement of the Wnt family of secreted signalling molecules in regulating the behaviour of ES cells. Activation of canonical Wnt signalling has been shown to either inhibit or promote the differentiation of ES cells into neurons, depending on the stage of differentiation. Therefore, looking at the expression profiles of all members of the family gene during the process would be a first step in determining whether or not Wnts may be involved in neural differentiation of ES cells in vitro. In this study, the expression of all 19 Wnt genes during the process is described. Neural differentiation was induced through the formation of embryoid bodies (EBs) in the absence of leukemia inhibitory factor (LIF) followed by the addition of retinoic acid (RA) for four days. Expression of Wnts was screened in five different stages during the process. Many Wnt genes exhibit dynamic RNA expression profiles during the process with a large proportion was observed to be at highest levels during later stages of differentiation, suggesting a complex pattern of Wnt functions during the process.